Optimization and modeling of microwave-assisted extraction of active compounds from cocoa leaves / Chan Chung Hung - Chan, Chung Hung (2013)
Microwave-assisted extraction (MAE) is a promising technique for extraction of active compounds from plants and it has the potential to be commercialized. However, due to limited significant parameters to describe the MAE process, optimization and modeling of MAE for scaling up are challenging and restricted. To resolve the problem, two intensive energy-related parameters, i.e. absorbed power density (APD) and absorbed